Analysis of the Talbot effect in apodized diffractive optical elements - Osuch, Tomasz; Jaroszewicz, Zbigniew (Photonics Letters of Poland, 2009)
This paper shows numerical results of the Talbot effect appearing behind an apodized phase mask. The field distributions in the self-image plane as well as in other characteristic planes are examined drawing on scalar diffraction theory and modified convolution approach. Simulation results show interesting properties of field distributions behind diffractive optical element with variable phase step height. The novelty of the article lies in examination of the self-image phenomenon in fibre Bragg gratings fabrication. Full Text: PDF References: H. F. Talbot, Philos. Mag. 9, 401, (1836). L. Rayleigh, Philos. Mag. 11, 196 (1881). K. Patorski, "The self-imaging phenomenon and its application", Progress in Optics 27, (North-Holland, Amsterdam, 1989). J. F. Barrera, R. Henao, Z. Jaroszewicz, A. Kołodziejczyk, "Talbot effect for periodical objects limited by finite apertures: a new interpretation", Optik 116, 144 (2005).[CrossRef] C. Gomez-Reino, M. T. Flores-Arias, M. V. Perez, C. Bao, "Fractional and integer Talbot effect for off-axis illumination and for finite object dimension in tapered GRIN media", Opt. Commun. 183, 365 (2000).[CrossRef] G. Shirripa Spagnolo, D. Ambrosini, Meas. Sci. Technol. 11, 77 (2000).[CrossRef] A. W. Lohmann, J. A. Thomas, "Talbot effect application: measurement of distance with a Fourier-transform method", Appl. Opt. 29, 4337 (1990).[CrossRef] V. Arrizon, J. Ojeda- Castaneda, "Irradiance at Fresnel planes of a phase grating", JOSA 9, 1801, (1992).[CrossRef] J. P. Guigay, Opt.Acta 18, 677 (1971). Z. Jaroszewicz, A. Kołodziejczyk, A. Kowalik, R. Restrepo, Optik 111, 207 (2000) B. Malo, S. Theriault, D.C. Johnson, F. Bilodeau, J. Albert, K.O. Hill, "Apodised in-fibre Bragg grating reflectors photoimprinted using a phase mask", Electron. Lett. 31, 223 (1995).[CrossRef] R. Kashyap, Fiber Bragg Gratings (Academic Press, 1999). J. W. Goldman, Introduction to Fourier optics (McGraw-Hill, New York, 1968). M. Sypek., "Light propagation in the Fresnel region. New numerical approach", Opt. Commun. 116, 43 (1995).[CrossRef] M. Sypek, C. Prokopowicz, M. Górecki, "Image multiplying and high-frequency oscillations effects in the Fresnel region light propagation simulation", Opt. Eng. 42, 3158 (2003).[CrossRef] T. Osuch, Z. Jaroszewicz, A. Kołodziejczyk, "Width of the apodization area in the case of diffractive optical elements with variable efficiency", Proc SPIE 6187, 61871, (2006).[CrossRef] T. Osuch, Z. Jaroszewicz, A. Kowalik, EOS Topical Meeting on Diffractive Optics 2010, Koli, Finland, 14-18 February, (2010) accepted for publication. T. Osuch, Z. Jaroszewicz, EOS Topical Meeting on Diffractive Optics 2007, Barcelona, Spain 20-23 November, 212 (2007).